Lactobacillus acidophilus versus placebo in the symptomatic treatment of irritable bowel syndrome: the LAPIBSS randomized trial - Sadrin, S.; Sennoune, S. R.; Gout, B.; Marque, S.; Moreau, J.; Grillasca, J.; Pons, O.; Maixent, J. M. (Cellular and Molecular Biology, 2017)
Irritable bowel syndrome is a chronic functional gastrointestinal disorder characterized by abdominal pain/discomfort and altered bowel habits. The use of Lactobacilli as probiotics during irritable bowel syndrome is based on their interesting mechanisms of action and their excellent safety profile but little is known about their clinical efficacy due to the lack of adequately designed clinical trials. The current clinical trial protocol aims to determine the effects of a mixture of Lactobacillus acidophilus NCFM and LAFTI L10 as probiotics to improve irritable bowel syndrome symptoms (LAPIBSS). Eighty patients with a positive diagnosis of irritable bowel syndrome according to Rome III criteria were recruited to a multicentre, double-blinded, in parallel groups, placebo-controlled randomized trial. Patients were provided with a daily dose of two capsules with two strains of Lactobacilli (5x109cfu/capsule) or placebo for 8 weeks on a 1:1 ratio. The primary outcome is to obtain scores of abdominal pain/discomfort assessed with a 100-mm visual analogue scale. The secondary outcome is to obtain scores of bloating, flatus and rumbling tested with a 100-mm visual analogue scale, composite score, stool frequency and stool consistency/appearance assessed with the Bristol Stool Form scale. According to the hypothesis that abdominal pain is mainly the result of a visceral hypersensitivity, the current study protocol aims to provide high quality proof of concept data to elucidate the efficacy of a consumption of a mixture of Lactobacillus acidophilus probiotic strains after 8 weeks, for decreasing abdominal pain. Ethical approval was given by ethics committee French Consultative Committee for the Protection of Individuals in Biomedical Research of the South West (Number CPP08-014a) and ANSM (French National Agency for Medicines and Health Products Safety – Number B80623-40). The findings from LAPBISS will be disseminated through peer-reviewed publications and at scientific conferences. Trial registration: EudraCT N°2008-A00844-51